Foraging behaviour by an intraguild predator blowfly, Chrysomya albiceps (Diptera : Calliphoridae) - Faria, Lucas D. B.; Reigada, Carolina; Trinca, Luzia A.; Godoy, Wesley A. C. (Springer, 2007)
Optimal foraging theory assumes that predators use different prey types to maximize their rate of energetic gain. Studies focusing on prey preference are important sources of information to understand the foraging dynamics of Chrysomya albiceps. The purpose of this investigation is to determine the influence of larval starvation in C. albiceps on the predation rate of different prey blowfly species and instars under laboratory conditions. Our results suggest that C. albiceps prefers Cochliomyia macellaria larvae to Chrysomya megacephala under non-starvation and starvation conditions. Nevertheless, predators gained more weight consuming C. macellaria. This result suggests that C. albiceps profit more in consuming C. macellaria rather than C. megacephala. The foraging behaviour displayed by C. abiceps on their prey and the consequences for the blowfly community are also discussed.
Keywords: foraging behavior; intraguild predator; prey preference; larval weight gained; Chrysomya albiceps